Findings Related to Cerebrospinal Fluid and Central Nervous System Disorders in Small Ruminants—A Retrospective Study on Sheep and Goats - Leandra C. Schöb; Christian Gerspach; Martina Stirn; Regina Hofmann-Lehmann; Barbara Riond (Animals, 2023)
Background: Small ruminants often suffer from central nervous system (CNS) disorders, and cerebrospinal fluid (CSF) analysis can be used as a diagnostic tool in this regard. In small animals and cattle, specific CSF patterns have been defined for specific disease categories. No data exist regarding CSF results obtained from small ruminants and their association with certain CNS diseases. Objectives: The objective of this study was to retrospectively investigate CSF findings obtained from sheep and goats and to identify possible CSF patterns associated with disease categories. Methods: CSF samples and medical records from 44 sheep and 27 goats were included in this study. All animals were presented to the Veterinary Teaching Hospital Zurich of the Veterinary Teaching Hospital Zurich of the Vetsuisse Faculty of the University of Zurich between 2003 and 2016 and had either a confirmed CNS diagnosis or showed CSF changes without a specific CNS diagnosis. Results: Mixed mononuclear pleocytosis was the most common CSF pattern in sheep (25%), followed by monocytic pleocytosis (21%). Lymphocytic pleocytosis was most frequently found in goats (37%). In 75% of sheep and 56% of goats, infectious CNS diseases were diagnosed, with listeriosis being the most common infectious disease in both species, followed by parasitic disorders (nematodiasis and coenurosis). Conclusions: The cytologic CSF patterns in small ruminants are mainly based on the increased presence of monocytic and lymphocytic cells with variable quantitative expression, whereas neutrophilic pleocytosis and cytoalbuminologic dissociation were rare findings. Infectious diseases of bacterial origin were the most common underlying causes for CSF alterations in sheep and goats, followed by parasitic disorders. The pleocytosis type is not helpful for differentiating disease types.